Useful technologies for doubling farmers income - S., Vithlani Nipa (Indian Farming, 2018)
Doubling real income of farmersby 2022 is a formidable task but itcan be possible only through theproper implementation of theappropriate strategies. Public R & Dinstitutions should be supported todevelop capacity in areas oftechnologies such as biotechnologywhich appear to have great potential.Farming is a skilled-profession andhence people could be skilled andmotivated through variousskill-development programmes of thegovernment. Lucrative avenues canbe created for those who want toleave agriculture and incentives andskills those who want to enter/continue this occupation. Higherprice realization by farmers need tobe achieved through various pricerealization market reforms likee-NAM and various provisions ofAPMC Act. Promotion of initiativeslike Soil-health Card, ICT-basedagricultural extension, formation ofFPO’s, Integrated Farming System.Concerted and well – coordinatedefforts are required to be madebetween the centre and the states.